Endothelial Glycocalyx Shedding Occurs during Ex Vivo Lung Perfusion: A Pilot Study. (25th August 2019) - Sladden, Timothy M.; Yerkovich, Stephanie; Wall, Douglas; Tan, Maxine; Hunt, William; Hill, Jonathan; Smith, Ian; Hopkins, Peter; Chambers, Daniel C.
Abstract : Background . Damage to the endothelium has been established as a key pathological process in lung transplantation and ex vivo lung perfusion (EVLP), a new technology that provides a platform for the assessment of injured donor lungs. Damage to the lung endothelial glycocalyx, a structure that lines the endothelium and is integral to vascular barrier function, has been associated with lung dysfunction. We hypothesised that endothelial glycocalyx shedding occurs during EVLP and aimed to establish a porcine model to investigate the mechanism underlying glycocalyx breakdown during EVLP. Methods . Concentrations of endothelial glycocalyx breakdown products, syndecan-1, hyaluronan, heparan sulphate, and CD44, were measured using the ELISA and matrix metalloproteinase (MMP) activity by zymography in the perfusate of both human ( n  = 9) and porcine ( n  = 4) lungs undergoing EVLP. Porcine lungs underwent prolonged EVLP (up to 12 hours) with perfusion and ventilation parameters recorded hourly. Results . During human EVLP, endothelial glycocalyx breakdown products in the perfusate increased over time. Increasing MMP-2 activity over time was positively correlated with levels of syndecan-1 ( r  = 0.886;p = 0.03 ) and hyaluronan ( r  = 0.943;p = 0.02 ). In the porcine EVLP model, hyaluronan was the only glycocalyx product detectable during EVLP (1 hr: 19 (13–84) vs 12 hr: 143 (109–264) ng/ml;p = 0.13 ). Porcine hyaluronan was associated with MMP-9 activity ( r  = 0.83;p = 0.02 ) and also with dynamic compliance ( r  = 0.57;p = 0.03 ). Conclusion . Endothelial glycocalyx products accumulate during both porcine and human EVLP, and this accumulation parallels an accumulation of matrix-degrading enzyme activity. Preliminary evidence in our porcine EVLP model suggests that shedding may be related to organ function, thus warranting additional study.